Pengembangan Aplikasi Monitoring Kartu Menuju Sehat (KMS) Terintegrasi berbasis Mobile - Giga Setiawan; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Posyandu is a Community-Based Health Effort (UKBM) organized from, by, for and with the people with the aim of prospering the community in the health sector. Those who manage posyandu consist of nutritionists, midwives and cadres. One of a kind is the toddlers posyandu which only serves patients under five years old. At the posyandu a monthly activity will be held in the form of checking the condition of infants. In the checking process there are stages of measurement, recording and reporting. There are many cases of losing books or losing KIA books so the data cannot be updated. With this problem the KMS recording and reporting system was built. It is expected that with this system the possibility of losing KIA books will decrease and the possibility of data errors will also decrease. This system was built using the Android operating system and using the waterfall SDLC (Software Development Life Cycle). This system chose the Android operating system because mobile devices are practical and easy to carry everywhere. If the user loses the smartphone, data about the child's growth is stored on the database server. This system uses MySQL as a database and volley to move data from the database to the system or vice versa using the PHP language. In the needs analysis process, there are 9 functional needs and involve 2 actors namely guest and member. In the implementation process using the Java language as the basic language of the Android operating system. Whereas the testing process uses 2 types of testing namely white box and black box. White box testing uses 2 methods, namely unit testing and integration testing. Black box testing uses a validation testing method to test every need.